Contemporary Legal Accountability Reform in Public Procurement: A Framework Integrating Ethical Norms and Anti-Corruption Mechanisms - Jawade Hafidz; Muhammad Dias Saktiawan; Agus Prasetia Wiranto; Aditya Noviyansyah; Ahmed Kheir Osman (Faculty of Sharia, IAIN Metro, 2025)
Government procurement of goods and services is a strategic sector that is vulnerable to irregularities and corruption. Therefore, reforming legal accountability in this area is crucial to creating governance that is clean, transparent, and has integrity. This study offers an alternative approach to public procurement reform by integrating Islamic principles as an ethical and normative foundation for building a sound governance system and an anti-corruption framework. This research uses a normative-qualitative method, analyzing various legal documents, Islamic literature, and modern governance theories. It focuses on fundamental Islamic values such as ʿadalah (justice), amanah (honesty and responsibility), maslahah (public welfare), and hisbah (social oversight). These values are highly relevant for addressing accountability challenges in public procurement. The findings show that applying these principles can strengthen the ethical dimension of procurement regulations, improve transparency in the tender process, and clarify public accountability mechanisms. The integration of Islamic values is not intended to replace existing positive law but to enrich and complement the legal framework with a moral and spiritual approach rooted in Islamic legal tradition. Academically, this study contributes by providing a new conceptual framework that combines Islamic ethical norms with public governance and anti-corruption law. This approach creates space for dialogue between Islamic legal tradition and modern legal practice, offering a more holistic solution to corruption issues in public procurement.